Effectiveness of massage therapy on post-operative outcomes among patients undergoing cardiac surgery: A systematic review - C. Ramesh; Vasudev Baburaya Pai; Nitin Patil; Baby S. Nayak; Anice George; Linu Sara George; Elsa Sanatombi Devi (Elsevier, 2015)
The incidence and prevalence of cardiovascular disease (CVD) are increasing rapidly in developing countries. Most patients with CVD do not respond to medical treatment and have to undergo cardiac surgery. This highly stressful experience results in increased levels of anxiety for patients. The objective of this review was to evaluate the efficacy of massage therapy on postoperative outcomes among patients undergoing cardiac surgery. A comprehensive literature search was made on PubMed-Medline, CINAHL, Science Direct, Scopus, Web of Science and the Cochrane library databases for original research articles published between 2000 and 2015. Original articles that reported the efficacy of massage therapy in patients undergoing cardiac surgery were included. The Cochrane data extraction form was used to extract data. A total of 297 studies were identified in the literature search. However, only seven studies were eligible for analysis. Of the seven studies, six studies demonstrated the effects of massage therapy on improving post-operative outcomes of patients, while one study found no evidence of improvement. Although the methods varied considerably, most of the studies included in this review reported positive results. Therefore, there is some evidence that massage therapy can lead to positive postoperative outcomes. Evidence of the effectiveness of massage therapy in patients undergoing cardiac surgery remains inconclusive. Additional research is needed to provide a strong evidence base for the use of massage therapy to improve post-operative outcomes and recovery among cardiac surgery patients